Catalisadores derivados de óxidos do tipo perovskita LaMO3, LaMFeO3 e LaMO3/γ-Al2O3 (M = Co, Ni ou Fe) aplicados à reforma a vapor de etanol - Faustino, Patrícia Brígida (Universidade Federal de São Carlos, 2014)
The hydrogen production has been extensively studied as a clean and powerful energy source, indicating that in the future hydrogen will became a key component for the global energy production, since burning fossil fuels, used nowadays, emits disturbing amounts of gases that cause the greenhouse effect and the global warming, which urgently needs to be reduced. Thus, hydrogen use has been studied as electric power generation and as a fuel derived from, for example, fuel cells that are able to convert chemical energy from the reaction between H2 and O2 into electrical energy, thermal energy and water, without causing environmental impacts, since it has no noises or vibrations and there is neither combustion or emission of particulates. A feasible way to produce hydrogen is the Steam Reforming Reaction of ethanol, since ethanol is a renewable source obtained mainly from sugar cane and also due to the low costs of operation in the Steam Reforming Reaction. Due to these facts, the reactions of Steam Reforming of Ethanol (SRE) have been extensively studied in previous years, and several studies have shown that this reaction provides a high hydrogen production; however, some parallel reactions may occur, forming side products, leading to reduced amounts of produced H2. Thus, the development of appropriate catalysts in these reactions becomes necessary, in a way that it enhances the conversion favoring the major product and suppressing the conversion to side products. A good efficiency of perovskite type oxides as catalysts in the SRE has been reported in several studies. These materials are mixed oxides with an ABO3 chemical structure, A being the largest cation such as alkali metals, alkaline earth metals and rare earth elements, and B representing the smallest cation such as transition metals. The partial substitution of cations located in the B site by others with similar oxidation state can promote changes in the redox properties of these ions, causing changes in the stability of the crystal structure. Therefore, the perovskite type oxides LaNiO3, LaCoO3 and LaFeO3 were synthesized through the citrate and precipitation methods. In a second stage Fe was added into the structure of the oxides LaNiO3 and LaCoO3, and in a new stage LaNiO3, LaCoO3 and LaFeO3 was synthesized with perovskite type oxides supported on gamma alumina by precipitation-deposition. After the syntheses, the catalysts were characterized and the influence of the preparation method was studied, specifically the effect of Fe addition and of the support presence, in relation to the activity of the catalysts in the reactions of steam reforming of ethanol for hydrogen production. The experimental results showed that the LaCoO3 catalyst synthesized by precipitation method was more active and stable than the others, although the LaNiO3 (citrate and precipitation) and LaCoO3 (citrate) catalysts had also been active in SRE. The material LaFeO3 showed to be inactive in the reaction. The Fe addition in the catalysts LaNiO3 and LaCoO3 structure did not significantly alter their catalytic performance, indicating an economically advantageous feature, since iron is a cheaper metal than cobalt and nickel, and may partially replace these elements in the catalyst formulation, thus decreasing the synthesis cost without compromising the hydrogen yields. The use of gamma alumina as support in the SRE favored materials with higher specific surface area, whereas it did not favor a higher activity or stability of these catalysts, however the activity was maintained.
Keywords: Catálise; Etanol; Energia; Hidrogênio; Ethanol; Steam reforming; Catalysts; Perovskites; Hydrogen; ENGENHARIAS::ENGENHARIA QUIMICA